Quality-of-life evaluation in chronic wounds: comparative analysis of three disease-specific questionnaires - Tricia Price (International Wound Journal, 2017)
The study directly compared the feasibility and performance of three instruments measuring health‐related quality of life (HRQoL) in chronic ulcers: the Freiburg Life Quality Assessment for wounds (FLQA‐w), the Cardiff Wound Impact Schedule (CWIS) and the Würzburg Wound Score (WWS). The questionnaires were evaluated in a randomly assigned order in a longitudinal observational study of leg ulcer patients. Psychometric properties (internal consistency, responsiveness and construct validity) were analysed. Patient acceptance was recorded. Analysis of n = 154 patients revealed good internal consistency (Cronbach's alpha ≥ 0·85) for all instruments. There were minor floor effects in all questionnaires (<1%) and some ceiling effects in the CWIS. Construct validity was satisfactory, for example, correlation with EuroQoL‐5D was r = 0·70 in the FLQA‐w, r = 0·47/0·67/0·68 in the CWIS dimensions and r = 0·60 in the WWS. The proportion of missing values was higher in the CWIS, and overall patient acceptance was highest in the FLQA‐w for wounds (54% best preferences) and lowest in the WWS (14%). In conclusion, the FLQA‐w, the CWIS and the WWS are reliable, sensitive and valid instruments for the assessment of HRQoL in leg ulcers. However, they show differences in clinical feasibility and patient acceptance.